Investigation of hot plume impact on space launch vehicle aft-body flows - Schumann, Jan-Erik; Justus Liebig University Giessen (My University, 2022)
The transonic flow around generic space launch vehicle aft-body geometries is investigated numerically using hybrid RANS-LES methods. A sensitivity study shows that the qualitative results are mostly insensitive to changes in grid resolution and numerical settings, but certain aspects such as circumferential grid resolution and LES filter length definition can affect the obtained quantitative results. It is further found that the presence of a plume leads to the appearance of an additional spectral contribution in the flow. The main investigations showed that changing the plume properties leads to a downstream shift of the reattachment location due to the stronger acceleration of the external flow. An increased wall temperature leads to a similar shift that is attributed to the slower development of turbulent structures in higher temperature shear layers. As a consequence the pressure fluctuations and the nozzle forces are reduced as well. However, the underlying flow phenomena are unaffected by the plume properties and wall temperature, with the exception of an additional spectral feature in the pressure fluctuations due to the interaction of shear layer movement and nozzle flow plume separation once the reattachment occurs mostly beyond the nozzle lip. A shorter nozzle strongly affects the recirculation region shape, pressure fluctuations and nozzle forces and does not show the observed flow phenomena observed for the longer nozzle configuration.
Keywords: Computation Fluid Dynamics; Turbulence; Aft-body flows; Scale resolving simulations; ddc:600